Viral contamination in cell culture: analyzing the impact of Epstein Barr virus and Ovine Herpesvirus 2 - Bastawecy, Iman M.; Abdelmonem, Mohamed; Afify, Ahmed F.; Saad, Norazalina; Shirosaki, Yuki; Abdullah, Che Azurahanim Che; El Naggar, Rania F.; Rohaim, Mohammed A.; Munir, Muhammad (Frontiers in Microbiology, 2025)
Cell culture techniques are increasingly favored over animal models due to rising costs, time constraints, and ethical concerns regarding animal use. These techniques serve critical roles in disease modeling, drug screening, drug discovery, and toxicity analysis. Notably, cell cultures facilitate primary virus isolation, infectivity assays, biochemical studies, and vaccine production. However, viral contamination in cell cultures poses significant challenges, particularly due to the necessity for complex and sophisticated detection methods. Among the prevalent viruses, Epstein Barr virus (EBV) is ubiquitous across human populations, infecting approximately 98% of individuals. Despite its prevalence, the detection of EBV is often not considered a safety priority, as its detection methods are well-established, including PCR assays that can identify both active and latent forms of the virus. Conversely, ovine herpesvirus 2 (OvHV-2), a relative of EBV, presents a critical concern due to its ability to infect a wide range of organs and species, including over 33 animal species and nearly all domestic sheep. This makes the detection of OvHV-2 crucial for the safety of cell cultures across various species. The literature reveals a gap in the comprehensive understanding of both EBV and OvHv-2 detection in cell culture systems, highlighting an urgent need for developing robust detection methodologies specific to EBV and OvHv-2 to ensure bioprocess safety.